2021
DOI: 10.1039/d0ra10796d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the H/D isotope effect of CH4/CD4 adsorption on a Rh(111) surface using a combined plane wave and localized basis sets method

Abstract: Using our CPLB method, we elucidate that the adsorption distance and adsorption energy of CH4 on the Rh(111) surface are shorter and larger than those of CD4, which is in reasonable agreement with the corresponding H/D isotope trend in experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To analyze the H/D isotope effects on ice surfaces, the MC_MO method was used for the ice surface and water molecules assigned to the model component, which was developed as an algorithm that can adequately describe H/D isotope effects by incorporating nuclear quantum effects. Prior studies have reported the successful application of the CPLB method in analyzing H/D isotope effects in the adsorption of CH 4 /CD 4 on a Rh(111) surface and H atoms on a Pd(111) surface. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the H/D isotope effects on ice surfaces, the MC_MO method was used for the ice surface and water molecules assigned to the model component, which was developed as an algorithm that can adequately describe H/D isotope effects by incorporating nuclear quantum effects. Prior studies have reported the successful application of the CPLB method in analyzing H/D isotope effects in the adsorption of CH 4 /CD 4 on a Rh(111) surface and H atoms on a Pd(111) surface. , …”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have reported the successful application of the CPLB method in analyzing H/D isotope effects in the adsorption of CH 4 /CD 4 on a Rh(111) surface and H atoms on a Pd(111) surface. 37,38 Computational Details. In this study, we utilized the implemented Gaussian16 software for MC_MP2 and MC_B3LYP-D3 calculations, 39,40 which incorporate Grimme's empirical dispersion term extended to B3LYP calculations to account for dispersion effects.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%
“…12,23 Theoretical methods and gas chromatography have found that the isotopic difference in CH 4 and CD 4 stems from the difference in polarizability and length of the C−H and C−D bonds; however, no studies have reported how this difference might translate into its sticking probability. 12,24,25 Studying CH 4 and CD 4 adsorption is an excellent model system to determine how slight mass differences in the condensate and projectile can impact adsorption and surface abundance of isotopic species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interstellar methane is the most common hydrocarbon, existing in both the gaseous and the solid form. Methane is commonly found in the gaseous planetary atmospheres or as molecular ices intermixed with water ice matrices. , As the most basic hydrocarbon, CH 4 serves as a base for addition reactions which form larger hydrocarbon species . Additionally, the isotopic twin of CH 4 , CD 4 , can serve as a model for understanding the effects and the abundance of deuterium within these environments. , Theoretical methods and gas chromatography have found that the isotopic difference in CH 4 and CD 4 stems from the difference in polarizability and length of the C–H and C–D bonds; however, no studies have reported how this difference might translate into its sticking probability. ,, Studying CH 4 and CD 4 adsorption is an excellent model system to determine how slight mass differences in the condensate and projectile can impact adsorption and surface abundance of isotopic species.…”
Section: Introductionmentioning
confidence: 99%
“…We had previously confirmed the efficiency of the CPLB method for analyzing the H/D isotope effect with respect to atomic and molecular adsorption on metal surfaces. 54,55 In this study, to understand the mechanism of the H-D exchange reaction on metal surfaces, we focused on the H/D isotope effect in the case of the adsorption properties of H 2 O/D 2 O and their dissociated OH/OD and H/D species on the Pt(111) surface. The geometrical and energetic changes induced by the H/D isotope effect were analyzed using the CPLB method.…”
mentioning
confidence: 99%